Knowledge worlds : media, materiality, and the making of the modern university - Martin, Reinhold, 1964- (Columbia University Press, 2021)
"What do the technical practices, procedures, and systems that have shaped institutions of higher learning in the United States, from the Ivy League and women's colleges to historically black colleges and land-grant universities, teach us about the production and distribution of knowledge? Addressing media theory, architectural history, and the history of academia, Knowledge Worlds reconceives the university as a media complex comprising a network of infrastructures and operations through which knowledge is made, conveyed, and withheld. Reinhold Martin argues that the material infrastructures of the modern university-the architecture of academic buildings, the configuration of seminar tables, the organization of campus plans-reveal the ways in which knowledge is created and reproduced in different kinds of institutions. He reconstructs changes in aesthetic strategies, pedagogical techniques, and political economy to show how the boundaries that govern higher education have shifted over the past two centuries. From colleges chartered as rights-bearing corporations to research universities conceived as knowledge factories, educating some has always depended upon excluding others. Knowledge Worlds shows how the division of intellectual labor was redrawn as new students entered, expertise circulated, science repurposed old myths, and humanists cultivated new forms of social and intellectual capital. Combining histories of architecture, technology, knowledge, and institutions into a critical media history, Martin traces the uneven movement in the academy from liberal to neoliberal reason"--